Growth and developmental aspects of credit allocation : an inquiry for leading countries and the Indian states - Das, Ramesh Chandra (Emerald Publishing Limited, 2023)
Growth and Developmental Aspects of Credit Allocation: An Inquiry for Leading Countries and the Indian States focuses on bank credit and deposit within a variety of economies and specifically examines Indian states to demonstrate how these two financial components are linked to their income growths and levels of development. Examining the world economy on both macro and micro levels, Ramesh Chandra Das highlights the increase in current world output as well as its implications for financial indicators and human development across selected countries. Focusing on credit-deposit ratios, trends of credit, NPA, GDP, security investments, and the interconnections of credit with GDP and HDI, Das further locates the link between the financial and real sectors of the economy that amplifies their overall progress. Undertaking a micro level study of these indicators across different states in India, chapters also provide insight into credit concentration, including security investment by banks and the inequality in credit allocation, within an Indian context. Incorporating and applying modern economic theory, Growth and Developmental Aspects of Credit Allocation: An Inquiry for Leading Countries and the Indian States presents a ground-breaking perspective for those interested in banking, finance, macro- and microeconomics, as well as human development on a global scale.
Keywords: Credit -- Developed countries.; Credit -- India.; Economic development -- Developed countries.; Economic development -- India.; Business & Economics -- Banks & Banking.; Credit & credit institutions.; elektronické knihy; electronic books